PP.41.19: RELATIONSHIP BETWEEN SERUM URIC ACID AND METABOLIC SYNDROME IN THE BRISIGHELLA HEART STUDY COHORT. (June 2015) - Cicero, A.F.G.; Parini, A.; Rosticci, M.; Cagnati, M.; Grandi, E.; D'Addato, S.; Borghi, C.; Group, Bhs
Abstract : Objective: Classically correlated with pathologies such as kidney stone and gout, today serum uric acid (SUA) seem to play a pivotal role in the cardiovascular disease risk. SUA is also strongly related to metabolic syndrome (MS) and its components. The aim of our study was to evaluate the SUA cut-off associated to the highest probability to detect a MS Design and method: We selected from the general database of the Brisighella Heart Study a sample of non-pharmacologically treated adult subjects, in primary prevention for cardiovascular disease, without known allergic nor rheumatological disease, not assuming antioxidant dietary supplements, visited during the same population survey. The SUA cut-off associated to the highest probability to detect a MS was investigated creating specific receiver operating characteristic (ROC) curves. Results: In our study median SUA levels were significantly higher in men (5, 1 mg/dL) than in women (3, 6 mg/dL) (p < 0.05). Splitting our cohort in 2 groups on the basis of SUA medians, we obtained 2 very different populations: if SUA levels were over the median the main cardiovasculardisease risk factors means were higher, while HDL cholesterol and apolipoprotein A1 levels were lower; these patients were more frequently affected by MS (58, 5%) and hypertension (52, 7%) than those with SUA levels under the median. The ROC curves showed that the SUA levels was a predictive test for the identification of those people affected by MS, with an AUC similar between men and women (6, 6 vs 6, 8, respectively); the cut off, by the way, were 5, 75 mg/dL in men and 3, 95 mg/dL in women. SUA levels seems to be the main determinant of MS both in men (OR = 1, 66; 95%CI 1, 23 – 1, 99) and women (OR = 1, 63; 95%CI 1, 19 – 1, 97). Conclusions: In our cohort SUA is strongly related to MS diagnosis, also for level lower than those usually considered normal.